Control of Boundary Layer over NACA0015 Using Fuzzy Logic by Suction Technique (Journal of University of Babylon for Engineering Sciences, 2018)
Re-attachment the separation of boundary layer using suction method is one of the important techniques, which improve the flow over bodies. This study focused on the design of fuzzy logic controller to control on the separation of the boundary layer, using suction delayed separation technique from the surface of NACA 0015 airfoil. The airfoil was designed and fabricated depending on the airfoil tool with (300x300) mm chord and span length respectively. The upper surface was developed with five holes  6mm diameter to suck the delayed boundary layer along the span of the airfoil about 75% from leading edge . Also there are four BMP180 Piezoelectric pressure sensors distributed with constant pitch on upper surface of model used to sense the pressure difference. Sub sonic wind tunnel with (300x300x 600) mm work section is used. (1.354, 1.915, 2.345, 2.708 and 3.028 x 105) Reynolds numbers and (0o, 3o, 6o, 9o, 12o, 15o, 16o and 17o) are the angles of attack were used as a conditions boundary of the experimental work. The model was tested without applying suction to determine the stall condition. Pneumatic vacuum cleaner with (0.00737 to 0.01329) discharge coefficient range was used to perform the suction experiment. Pressure difference and angle of attack were input of fuzzy logic controller which programmed by using commercial Matlab softwar. The results of applying suction showed an increase of 14.72% in the lift coefficient and increase the stall angle from 15o to more than 17o. Also lift/drag ratio increased when angle of attack increased. Fuzzy logic rules gave steady enhancement at range of suction coefficient CQ universally acceptable.